Pengaruh Paparan Sosial Media terhadap Perilaku Kesehatan Reproduksi Remaja Putri - Eka Faizaturrahmi; Nurannisa Fitria Aprianti (Program Studi D III Kebidanan Akademi Kesehatan Sapta Bakti Bengkulu, 2026)
The development of social media has significantly influenced various aspects of adolescents’ lives, including reproductive health behaviors. Adolescent girls are particularly vulnerable to the information circulating on social media, whether educational or inaccurate in nature. High levels of social media exposure may affect adolescents’ knowledge, attitudes, and behaviors related to reproductive health. This study aimed to analyze the influence of social media exposure on reproductive health behaviors among adolescent girls. A quantitative approach with a cross-sectional design was employed. Data were collected through questionnaires distributed to adolescent girls aged 15–18 years. The results showed that the majority of respondents had a high level of social media exposure (68.3%) and demonstrated good reproductive health behaviors (71.7%). Chi-Square analysis revealed a significant association between social media exposure and reproductive health behaviors among adolescent girls (χ² = 15.85; p = 0.001). Respondents with high social media exposure were more likely to exhibit better reproductive health behaviors compared to those with lower exposure. Furthermore, greater exposure to reproductive health educational content was associated with more positive reproductive health behaviors among respondents. Therefore, social media can serve as an effective medium for reproductive health education